KARTIKA's Strategy for the Free Health Check Program - Malaha, Adnan; Novitasari, Desi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Community participation in the Free Health Check (CKG) program still faces obstacles such as lack of information, limited time, and fear of knowing the test results. This study aims to analyze the effectiveness of youth collaboration strategies in increasing community participation in the CKG program in East Bulango District. The research design used a qualitative descriptive method with a case study approach. Initial data on June 13, 2025, showed 216 registrants with 214 people attending. After training for 20 youth as health promotion agents on August 2, 2025, and continued with promotions through social media and field activities, the number of registrants increased to 427 with 423 people attending by August 13, 2025. This increase is equivalent to a 97.6% increase in participation. These findings indicate that youth involvement is effective in expanding the reach of information and overcoming barriers to community participation. The results of the study emphasize the importance of youth-based collaborative strategies as agents of change in strengthening early detection and health promotion programs in the community.